Ecological aspects of using biological diesel oil in railway transport - Lingaitis, Leonas P.; Pukalskas, Saugirdas (Transport, 2008)
The number of various transport facilities used in Europe is rapidly growing. They release a big amount of pollutants into the atmosphere. Therefore, environment protection from these pollutants ejected by internal combustion engines is a key problem facing us today and which will be acute in the future. Biofuel is the only effective and widely used alternative fuel which can reduce pollution of the environment. The main aim of the present paper is to perform a comparative analysis of burnt gases of engines using rapeseed oil methyl ester and petroleum diesel oil and to determine ecological effectiveness of biofuel used in diesel locomotive engines in railway transport.First published online: 27 Oct 2010